Programming of properties applied to absorption refrigeration systems - Rodríguez Muñoz, José Luis; Pacheco Cedeño, Sergio; Zuno Silva, Jorge; Borja Soto, Carlos Ernesto (Ingenio y Conciencia Boletín Científico de la Escuela Superior Ciudad Sahagún, 2023)
This work aims to develop a computational model that helps to predict the thermodynamic properties of the CaCl2-LiBr-LiNO3-H2O mixture, which can be used for the analysis and simulation of absorption refrigeration systems. The study is based on the multiple interpolation methodology developed in the Engineering Equation Solver (EES) software and the values ​​obtained are compared with those obtained experimentally. The results show that the developed model adequately predicts the properties of vapor pressure, specific enthalpy, and specific heat and the maximum deviation percentages obtained are 9.34%, 0.027%, and 0.15%, respectively. In addition, the simulation results show that, for the same operating conditions, a COP error of 4.58% is obtained when the system operates at an effectiveness of 1.0 (100% of its capacity), while the smallest COP error of 1.02% is obtained at the effectiveness of 0.6 (60% of its capacity), in comparison with the results presented in the literature.